Myelin Oligodendrocyte Glycoprotein Antibody–Positive Optic Neuritis: Clinical Characteristics, Radiologic Clues, and Outcome - Chen, John J.; Flanagan, Eoin P.; Jitprapaikulsan, Jiraporn; López-Chiriboga, Alfonso (Sebastian) S.; Fryer, James P.; Leavitt, Jacqueline A.; Weinshenker, Brian G.; McKeon, Andrew; Tillema, Jan-Mendelt; Lennon, Vanda A.; Tobin, W. Oliver; Keegan, B. Mark; et al. (American journal of ophthalmology, 2018)
To characterize the clinical phenotype of myelin oligodendrocyte glycoprotein antibody (MOG-IgG) optic neuritis. Observational case series. Setting: Multicenter. Patient/Study Population: Subjects meeting inclusion criteria: (1) history of optic neuritis; (2) seropositivity (MOG-IgG binding index > 2.5); 87 MOG-IgG-seropositive patients with optic neuritis were included (Mayo Clinic, 76; other medical centers, 11). MOG-IgG was detected using full-length MOG-transfected live HEK293 cells in a clinically validated flow cytometry assay. Main Outcome Measures: Clinical and radiologic characteristics and visual outcomes. Fifty-seven percent were female and median age at onset was 31 (range 2–79) years. Median number of optic neuritis attacks was 3 (range 1–8), median follow-up 2.9 years (range 0.5–24 years), and annualized relapse rate 0.8. Average visual acuity (VA) at nadir of worst attack was count fingers. Average final VA was 20/30; for 5 patients (6%) it was ≤20/200 in either eye. Optic disc edema and pain each occurred in 86% of patients. Magnetic resonance imaging showed perineural enhancement in 50% and longitudinally extensive involvement in 80%. Twenty-six patients (30%) had recurrent optic neuritis without other neurologic symptoms, 10 (12%) had single optic neuritis, 14 (16%) had chronic relapsing inflammatory optic neuropathy, and 36 (41%) had optic neuritis with other neurologic symptoms (most neuromyelitis optica spectrum disorder–like phenotype or acute disseminated encephalomyelitis). Only 1 patient was diagnosed with MS (MOG-IgG-binding index 2.8; normal range ≤ 2.5). Persistent MOG-IgG seropositivity occurred in 61 of 62 (98%). A total of 61% received long-term immunosuppressant therapy. Manifestations of MOG-IgG-positive optic neuritis are diverse. Despite recurrent attacks with severe vision loss, the majority of patients have significant recovery and retain functional vision long-term.